The Role of Passion in Psychological and Cardiovascular Responses: Extending the Field of Passion and Positive Psychology in New Directions - Vallerand, Robert J.; Paquette, Virginie; Richard, Christine (Frontiers in Psychology, 2022)
The present study fills a void in research on passion by examining for the first time the role of passion in physiological responses. The aim of the study was to investigate the role of passion, and the mediating role of cognitive appraisals, in the psychological and physiological responses to a stressful situation related to one’s passion. Students (43 women, 12 men, M age = 27.21 years), who were passionate for their studies, completed the Passion Scale for their studies and the Cognitive Appraisal Scale (assessing perceptions of challenge/threat). Then, they engaged in an education task under stressful conditions, and a subsequent unrelated leisure task under no-stress. Physiological reactivity was measured throughout the entire session and their perceptions of situational vitality and positive and negative emotions were assessed directly after the education task. Results showed that harmonious passion positively predicted challenge appraisals that, in turn, were positively related to positive emotions, vitality, and positive cardiovascular adaptation while engaging in the stressful education task, but less so with the leisure task (unrelated to one’s passion for academia). On the other hand, obsessive passion positively predicted threat appraisals. In turn, threat appraisals were positively related to negative emotions, negatively associated with vitality, and not related to cardiovascular reactivity. The present findings suggest that harmonious passion creates the onset of an adaptive psychological and physiological response whereas the response is less adaptive with obsessive passion.